Convergence legislation and its impact in the European Union, the United Kingdom and South Africa - Kreuzer, Nicola (Department of Commercial Law, 2014)
After broadly defining convergence and giving examples of converging technologies this paper will examine how selected forms of convergent technologies work. An examination of how the different countries, South Africa in particular and the European Union, have responded on a legislative level to the convergence phenomenon is consequently preceded by some insight into the underlying techniques of convergence. Some benefits and disadvantages of the two different approaches will also be examined. This might be of interest to countries that have not yet decided on which approach to follow. Is convergence legislation really required and how far would it benefit the country? Has the South African convergence legislation been intelligently thought through? A large part of the telecommunications industry feels that the answer to these questions is in the negative.12 This paper seeks to give some guidelines in pondering on these issues.